Efficient preparation method of nano-copper rod and nano-copper rod

By adding diamine and hydrazine hydrate to the copper source aqueous solution, the reaction is controlled to 160°C, the problem of difficult control of the shape and size of nano copper wires is solved, the waste liquid treatment cost is reduced, and spherical/sheet particles are avoided The production of nano copper rods has achieved efficient preparation and efficient production.

CN119216571APending Publication Date: 2024-12-31JIYUAN XINGHAN NEW MATERIAL TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411353805.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The prior art is difficult to accurately control the form and size of nano-copper wires, and the wastewater generated in the high alkaline reaction system is costly, and it is difficult to avoid the formation of spherical/sheet-shaped particles in the nano-copper wires.

Method used

Using a copper source aqueous solution with a Cu2+ concentration of 0.5-2mol/L, a Cl- concentration of 1-5mol/L, and a pH ≤7, a specific diamine and hydrazine hydrate were added, and the temperature increase rate was controlled to 160°C, and the diameter was prepared by this method. The nanocopper rod of 300-850 nm avoids the formation of spherical/sheet-like particles and reduces the saline-alkali concentration in the reaction waste liquid.

Benefits of technology

Accurate control of the shape and size of nano copper wires is achieved, reducing the cost of waste liquid treatment, and the prepared nano copper rods contain almost no spherical/sheet-shaped particles, which are suitable for subsequent applications without grading, improving preparation efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119216571A_ABST
    Figure CN119216571A_ABST
Patent Text Reader

Abstract

The invention discloses an efficient preparation method of a nano-copper rod and the nano-copper rod. The preparation method comprises steps as follows: S1, a copper source aqueous solution with the Cu < 2 + > concentration being 0.5-2 mol / L, the Cl <-> concentration being 1-5 mol / L and the pH being smaller than or equal to 7 is prepared; S2, at least one diamine shown in the general formula H2N-X-NH2 is added to the copper source aqueous solution obtained in the step S1 and dispersed uniformly, X independently represents C2-C10 alkyl or C6-C10 aryl, and a precursor solution is obtained; the molar ratio of Cu < 2 + > to diamine is 1: (0.2-0.3); s3, adding hydrazine hydrate into the precursor solution obtained in the step S2, and uniformly dispersing to obtain a reaction solution; and S4, the reaction solution obtained in the step S3 is heated to 160 DEG C at the heating rate of 5-10 DEG C / min, a heat preservation reaction is conducted for at least 4 h, cooling and separation are conducted, and the nano-copper rod with the diameter being 300-850 nm is obtained. According to the method, the shape and the size of the nano-copper rod can be accurately controlled, the yield is high, and the method is suitable for batch industrial production. Correspondingly, the invention provides the nano-copper rod prepared by the method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of nanomaterial preparation, and in particular to an efficient preparation method of a nano copper rod and a nano copper rod. Background Art

[0002] Nano copper wires / nano copper rods are widely used in electronic devices due to their good conductivity and lower cost than precious metal silver. Different from granular / flaky copper powder, linear / fibrous nano copper wires are more difficult to grade and more expensive. Seeking a preparation method that can accurately control the morphology and size of nano copper wires has always been one of the research directions in this field.

[0003] Related art discloses a method for synthesizing copper nanowires by liquid phase method, which uses copper nitrate as a precursor, hydrazine hydrate as a reducing agent, and ethylenediamine as a protective agent under alkaline conditions at 60°C (Yu Chang; Mei Ling Lye; Hua Chun Zeng, Large-scale synthesis of high-quality ultra long copper nanowires. Langmuir: the ACS journal of surfaces and colloids 2005, 21, 3746-3748). However, this method requires precise control of the material ratio, and its high ethylenediamine / Cu ratio is not suitable for the synthesis of copper nanowires. 2+ Under the proportional conditions, granular / flaky copper particles are produced instead of linear / fibrous nano-copper rods. It is still difficult to accurately control the morphology and size of the product. In addition, this method also increases the salt and alkali concentration in the reaction wastewater by adding sodium hydroxide to the high-alkalinity reaction system, thereby increasing the cost of wastewater treatment.

[0004] Therefore, how to accurately control the shape and size of synthesized nano-copper rods remains a problem to be solved in this field. Summary of the invention

[0005] In order to accurately control the shape and size of nano copper wires, in a first aspect, the present invention provides an efficient preparation method for nano copper rods, which specifically adopts the following technical solutions.

[0006] An efficient preparation method of nano copper rods comprises the following steps:

[0007] S1. Preparation of Cu 2+ The concentration is 0.5-2mol / L, Cl - Aqueous solution of copper source with a concentration of 1-5 mol / L and pH ≤ 7:

[0008] S2, adding at least one diamine represented by the general formula H2N-X-NH2 to the copper source aqueous solution obtained in step S1 and dispersing it uniformly, wherein X independently represents a C2-C10 hydrocarbon group or a C6-C10 aromatic group, to obtain a precursor solution; Cu 2+ The molar ratio with diamine is 1:(0.2-0.3);

[0009] S3, adding hydrazine hydrate to the precursor solution obtained in step S2 and dispersing it evenly to obtain a reaction solution;

[0010] S4. The reaction solution obtained in step S3 is heated to 160° C. at a heating rate of 5-10° C. / min, and the reaction is kept at this temperature for at least 4 hours. The solution is cooled, and nano-copper rods having a diameter of 300-850 nm are separated.

[0011] By adopting the above technical solution, the morphology and size of the prepared nano copper wires can be accurately controlled. The obtained finished nano copper wires contain almost no spherical / flaky particles. The diameter of the nano copper wires is 300-850nm, and no additional classification is required for subsequent applications. The reaction system does not need to be added with alkaline agents such as sodium hydroxide to adjust the pH value to above 7, which greatly reduces the salt and alkali concentration in the reaction waste liquid and is conducive to waste liquid treatment. At the same time, experiments have found that when chloride ions and diamines are present in the reaction system at the same time, the nano copper wires obtained by heating to 160°C at 5-10°C / min and reacting for at least 4h have good size uniformity and almost no spherical / flaky particles.

[0012] Furthermore, in the copper source aqueous solution of step S1, the molar ratio of divalent copper ions to chloride ions is 1:(0.8-1.2). When the molar ratio of divalent copper ions to chloride ions is within the aforementioned range, it is more conducive to controlling the morphology and size of the nano-copper wires. Specifically, the molar ratio of divalent copper ions to chloride ions can be 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2, etc.

[0013] Furthermore, the copper source aqueous solution in step S1 is prepared by dissolving a water-soluble copper salt containing copper chloride in water. It is simpler to directly prepare a copper source aqueous solution containing copper ions and chloride ions by dissolving copper chloride in water. Accordingly, copper chloride and other copper salts can be compounded to prepare a copper source aqueous solution, or an appropriate amount of sodium chloride or other water-soluble chloride salts that do not participate in the reaction can be added to adjust the chloride ion concentration in the copper source aqueous solution.

[0014] Further, X represents a substituted or unsubstituted straight-chain alkyl group. Y may represent a substituted or unsubstituted divalent alkyl group, and as an example, the diamine may be ethylenediamine, propylenediamine, butylenediamine, and the like.

[0015] Furthermore, X represents -CH2-CH2-.

[0016] Furthermore, the diamine contains at least one diamine A represented by the general formula H2N-Y-NH2, Y independently represents a C2-C10 hydrocarbon group; and at least one diamine B represented by the general formula H2N-Z-NH2, Z independently represents a C6-C10 aromatic group. The aromatic diamine and the aliphatic diamine synergistically regulate the morphology and size of the nano copper wire for a better effect. Z can represent a C6-C10 substituted / position-substituted divalent aromatic group, such as phenyl, methylphenyl, naphthyl, etc. As an example, the diamine B can be o-phenylenediamine, 1,8-naphthalenediamine, 1,3-naphthalenediamine, etc.

[0017] Further, in step S2, after the diamine is added and dispersed evenly, the solution is heated to 75-85° C. and stirred continuously for 0.5-1.5 h.

[0018] Further, in step S3, the amount of hydrazine hydrate added is equal to that of Cu 2+ The molar ratio of hydrazine hydrate to Cu is (2-6):1. 2+ The molar ratio can be 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1, 6:1, etc.

[0019] Further, in step S4, after the reaction solution is cooled to room temperature, it is centrifuged at 5000 rpm for 5 minutes, washed alternately with deionized water and ethanol, and then centrifuged to separate the nano-copper rods, and dried to obtain finished nano-copper rods.

[0020] In a second aspect, the present invention provides a nano copper rod, which is prepared by the aforementioned method and has a diameter of 300-850 nm. The finished product contains almost no spherical / flaky particles, and the size of the nano copper wire is uniform and can be used without subsequent classification. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The scanning electron microscope of the nano copper rod obtained in the embodiment Figure 1 ;

[0022] Figure 2 The scanning electron microscope of the nano copper rod obtained in the embodiment Figure 2 . DETAILED DESCRIPTION

[0023] The present application is further described in detail below with reference to the embodiments.

[0024] Example

[0025] <Example 1>

[0026] An efficient preparation method of nano copper rods, the steps are as follows:

[0027] S1. Weigh cupric chloride dihydrate and dissolve it in water to prepare Cu 2+Aqueous copper source solution with a concentration of 0.5 mol / L, a Cl- concentration of 1 mol / L, and a pH of ≤7:

[0028] S2, add ethylenediamine to the copper source aqueous solution obtained in step S1 to disperse evenly, ethylenediamine and Cu 2+ The molar ratio of is 0.2:1 to obtain a precursor solution; then, the precursor solution is heated to 80° C. and stirred for 1 hour;

[0029] S3, add hydrazine hydrate to the precursor solution obtained in step S2 and disperse it evenly, hydrazine hydrate and Cu 2+ The molar ratio of is 2:1 to obtain a reaction solution;

[0030] S4, heating the reaction solution obtained in step S3 to 160°C at a heating rate of 5°C / min, and keeping the temperature for at least 4 hours; after the reaction solution is cooled to room temperature, centrifuge it at 5000 rpm for 5 minutes; wash it alternately with deionized water and ethanol for 3 times, centrifuge to separate the nano copper rods, and vacuum dry it in an oven at 60°C for 6 hours to obtain the finished nano copper rods.

[0031] <Example 2-4>

[0032] Examples 2-4 all relate to a highly efficient method for preparing nano copper rods, which are based on Example 1, except that the process parameters of each step are different, as shown in Table 1.

[0033] Table 1. Process parameters of Examples 1-4

[0034]

[0035] Examples 2-4 all produced fibrous nano-copper rods.

[0036] <Example 5>

[0037] An efficient preparation method of nano copper rods, the steps are as follows:

[0038] S1. Weigh copper chloride dihydrate and sodium chloride in a molar ratio of 2:1 and dissolve them in water to prepare Cu 2+ Aqueous copper source solution with a concentration of 2 mol / L, a Cl- concentration of 5 mol / L, and a pH of ≤7:

[0039] S2, add ethylenediamine to the copper source aqueous solution obtained in step S1 to disperse evenly, ethylenediamine and Cu 2+ The molar ratio of is 0.3:1 to obtain a precursor solution; then, the precursor solution is heated to 80° C. and stirred for 1 hour;

[0040] S3, add hydrazine hydrate to the precursor solution obtained in step S2 and disperse it evenly, hydrazine hydrate and Cu 2+ The molar ratio of is 6:1 to obtain a reaction solution;

[0041] S4, heating the reaction solution obtained in step S3 to 160°C at a heating rate of 5°C / min, and keeping the temperature for at least 4 hours; after the reaction solution is cooled to room temperature, centrifuge it at 5000 rpm for 5 minutes; wash it alternately with deionized water and ethanol for 3 times, centrifuge to separate the nano copper rods, and vacuum dry it in an oven at 60°C for 6 hours to obtain the finished nano copper rods.

[0042] <Examples 6-8>

[0043] Examples 6-8 are based on Example 2, with the difference that in step S1, the raw materials for preparing the copper source aqueous solution are different, and the chloride ion concentrations in the obtained copper source aqueous solution are different.

[0044] In Example 6, copper chloride dihydrate and copper nitrate were prepared with a molar ratio of 3:1. 2+ A copper source aqueous solution with a concentration of 1 mol / L, a Cl- concentration of 1.5 mol / L, and a pH of ≤7.

[0045] In Example 7, copper chloride dihydrate and copper nitrate were prepared with a molar ratio of 1.5:1. 2+ A copper source aqueous solution with a concentration of 1 mol / L, a Cl- concentration of 1.2 mol / L, and a pH of ≤7.

[0046] In Example 8, copper chloride dihydrate and copper nitrate were prepared with a molar ratio of 1:1. 2+ A copper source aqueous solution with a concentration of 1 mol / L, a Cl- concentration of 1 mol / L, and a pH of ≤7.

[0047] <Examples 9-11>

[0048] Examples 9-11 are based on Example 2, except that in step S4, the reaction solution is heated to 160° C. at different heating rates.

[0049] In Example 9, the heating rate is 6°C / min.

[0050] In Example 10, the heating rate is 8°C / min.

[0051] In Example 11, the heating rate is 10°C / min.

[0052] <Examples 12-15>

[0053] Examples 12-15 are based on Example 2, except that different diamines are added in step S2.

[0054] In Example 12, ethylenediamine was replaced with an equal molar amount of butanediamine.

[0055] In Example 13, the added diamine is a mixture of ethylenediamine and o-phenylenediamine, the molar ratio of ethylenediamine to o-phenylenediamine is 2:1, and the total molar amount of the added diamine remains unchanged.

[0056] In Example 14, the added diamine is a mixture of ethylenediamine and 1,8-naphthalenediamine, the molar ratio of ethylenediamine to 1,8-naphthalenediamine is 4:1, and the total molar amount of the added diamine remains unchanged.

[0057] In Example 15, the added diamine is a mixture of ethylenediamine and 1,3-naphthalenediamine, the molar ratio of ethylenediamine to 1,3-naphthalenediamine is 4:1, and the total molar amount of the added diamine remains unchanged.

[0058] Comparative Example

[0059] <Comparative Example 1>

[0060] Comparative Example 1 is based on Example 2, except that: in step S1, copper nitrate is used to prepare a copper source aqueous solution to obtain Cu 2+ A 2 mol / L copper source aqueous solution containing no chloride ions.

[0061] <Comparative Example 2-3>

[0062] Comparative Example 2-3 is based on Example 2, except that in step S2, the amount of ethylenediamine added is different.

[0063] In Comparative Example 2, ethylenediamine and Cu 2+ The molar ratio is 0.05:1.

[0064] In Comparative Example 3, ethylenediamine and Cu 2+ The molar ratio is 0.5:1.

[0065] <Comparative Examples 4-5>

[0066] Comparative Examples 4-5 are based on Example 2, except that in step S4, the reaction solution is heated to 160° C. at different heating rates.

[0067] In Comparative Example 4, the heating rate was 2°C / min.

[0068] In Comparative Example 5, the heating rate is 12°C / min.

[0069] Test results

[0070] <Nano copper rod morphology>

[0071] The particle morphology of the nano-copper rods prepared in each example was observed by scanning electron microscopy and the size of the nano-copper rods was calculated using software. The results are recorded in Table 2. Figure 1-2These are scanning electron microscope images of the nano-copper rods prepared in Example 2. It can be seen that the prepared nano-copper rods are fibrous and contain almost no spherical / flaky particles. Figure 2 It can be seen that the particle size of the very small amount of spherical / flaky particles is about 1.48 microns.

[0072] <Nano copper rod yield>

[0073] The volume and copper ion concentration of the prepared copper source aqueous solution were recorded, the prepared nano-copper rods were weighed, and the yield was calculated according to the following formula:

[0074]

[0075] The results are recorded in Table 2.

[0076] Table 2. Test results

[0077]

[0078]

[0079] Note: 0 means that the nano copper rods contain almost no spherical / flaky particles

[0080] From the test results, we can know that:

[0081] The diameter of the nano copper rods prepared in each embodiment is between 300-850nm, and almost no spherical / flaky copper powder particles are contained. The prepared nano copper rods are all fibrous, indicating that in the presence of chloride ions, the addition amount of diamine and the heating rate are controlled according to the method of the present invention, and the nano copper rods are prepared at 160°C. The morphology of the nano copper rods can be precisely controlled. The yield of the nano copper rods prepared in each embodiment is 26.6-36.6%, indicating that the method of the present invention has a high preparation efficiency and is suitable for mass industrial preparation of nano copper rods.

[0082] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. An efficient preparation method of nano copper rods, characterized in that The steps include: S1. Preparation of Cu 2+ Aqueous copper source solution with a concentration of 0.5-2 mol / L, a Cl- concentration of 1-5 mol / L, and a pH of ≤7: S2, adding at least one diamine represented by the general formula H2N-X-NH2 to the copper source aqueous solution obtained in step S1 and dispersing it uniformly, wherein X independently represents a C2-C10 hydrocarbon group or a C6-C10 aromatic group, to obtain a precursor solution; Cu 2+ The molar ratio with diamine is 1:(0.2-0.3); S3, adding hydrazine hydrate to the precursor solution obtained in step S2 and dispersing it evenly to obtain a reaction solution; S4. The reaction solution obtained in step S3 is heated to 160° C. at a heating rate of 5-10° C. / min, and the reaction is kept at this temperature for at least 4 hours. The solution is cooled, and nano-copper rods with a diameter of 300-850 nm are separated.

2. The efficient preparation method of nano copper rods according to claim 1, characterized in that: In step S1, in the copper source aqueous solution, the molar ratio of divalent copper ions to chloride ions is 1:(0.8-1.2).

3. The efficient preparation method of nano copper rods according to claim 2, characterized in that: Step S1: The copper source aqueous solution is prepared by dissolving a water-soluble copper salt containing copper chloride in water.

4. The efficient preparation method of nano copper rods according to claim 1, characterized in that: X represents a substituted or unsubstituted straight-chain alkyl group.

5. The efficient preparation method of nano copper rods according to claim 4, characterized in that: X represents -CH2-CH2-.

6. The efficient preparation method of nano copper rods according to claim 4, characterized in that: The diamine contains at least one diamine A represented by the general formula H2N-Y-NH2, where Y independently represents a C2-C10 hydrocarbon group; and at least one diamine B represented by the general formula H2N-Z-NH2, where Z independently represents a C6-C10 aromatic group.

7. The efficient preparation method of nano copper rods according to any one of claims 1 to 6, characterized in that: Step S2, after adding the diamine and dispersing it evenly, the solution is heated to 75-85° C. and stirred continuously for 0.5-1.5 h.

8. The efficient preparation method of nano copper rods according to any one of claims 1 to 6, characterized in that: Step S3, the amount of hydrazine hydrate added is equal to the amount of Cu 2+ The molar ratio is (2-6):

1.

9. The efficient preparation method of nano copper rods according to any one of claims 1 to 6, characterized in that: Step S4, after the reaction solution is cooled to room temperature, it is centrifuged at 5000 rpm for 5 minutes, washed alternately with deionized water and ethanol, and then centrifuged to separate the nano-copper rods, and dried to obtain finished nano-copper rods.

10. A nano copper rod, made by the method according to any one of claims 1 to 9.

Citation Information

Cited By

  • Preparation method of rod-like copper powder

    CN120961938A